Rancang Bangun Rumah Pintar (Smart Home) Berbasis Internet Of Things (IoT) - Malik Ibrahim; Bambang Sugiarto (Infotek: Jurnal Informatika dan Teknologi, 2023)
Control of electronic equipment can be done with a smart home application that controls web-based household electronic equipment and can be controlled remotely. This smart home application can make it easier for users to control household electronic equipment such as lights, air conditioners and so that it can reduce the wastage of electricity when users forget to turn off household electronic equipment when outside the home or wherever the user is. This application uses NodeMCU which functions as a server that will connect hardware and software controlled via the web as an interface used by users to enter input and produce output. From the results of the tests that have been carried out, this system can be controlled remotely using button commands and can function as originally intended for this research.